Contemporary Painting: Anjani Mystery Room - BR.PURBA, RIPASE NOSTANTA (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2021)
Abstract painting is a genre of art whose forms of delivery are not direct. Anjani is one of the young artists who work with abstract paintings by displaying her wild imagination. Through a mix of media mix and sweep, spill, melt scratch techniques together and connect together into an unexpected configuration of results. The artist himself has dyslexia, which is not trivial for someone, especially artists because dyslexia is a 'language disorder' which causes individual deferences. However, lack is not an obstacle to Anjani, Anjani makes her shortcomings into an artistic 'personal charm' and this is a great capital and impetus for creating the best work of art. The theory used is Paul Ricoeur's interpretation theory. Interpretation is the interpretation, meaning, meaning, impression, opinion, and theoretical view of an object, the object this time meant is Anjani's painting, which the author limits to three paintings, namely Regeneration, Shifting, Mandala. Lukisan Abstrak, Paul Recoeur, Hermeneutik, Disleksia.